2007
DOI: 10.1007/s10811-006-9148-1
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nitrogen and phosphorus from wastewater using microalgae immobilized on twin layers: an experimental study

Abstract: Removal of nitrogen and phosphorus from wastewater by two green microalgae (Chlorella vulgaris and Scenedesmus rubescens) was investigated using a novel method of algal cell immobilization, the twin-layer system. In the twin-layer system, microalgae are immobilized by self-adhesion on a wet, microporous, ultrathin substrate (the substrate layer). Subtending the substrate layer, a second layer, consisting of a macroporous fibrous tissue (the source layer), provides the growth medium. Twin-layers effectively sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
3
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(149 citation statements)
references
References 30 publications
7
132
3
7
Order By: Relevance
“…In the range of light intensity from 10 to 100 lmol m -2 s -1 , the growth rate almost linearly increased to about 6 g m -2 day -1 with the increase of light intensity. This growth is much greater than that in Johnson and Wen [20], Shi et al [15] and Shen et al [25]. Beyond 100 lmol m -2 s -1 , the biofilm growth rate was maintained to be almost the same.…”
Section: The Effect Of Light Intensitymentioning
confidence: 63%
See 1 more Smart Citation
“…In the range of light intensity from 10 to 100 lmol m -2 s -1 , the growth rate almost linearly increased to about 6 g m -2 day -1 with the increase of light intensity. This growth is much greater than that in Johnson and Wen [20], Shi et al [15] and Shen et al [25]. Beyond 100 lmol m -2 s -1 , the biofilm growth rate was maintained to be almost the same.…”
Section: The Effect Of Light Intensitymentioning
confidence: 63%
“…Some similar cultivation methods investigated by other research groups showed potential advantages in effluent treatments, biomass accumulation, and harvest. Shi et al [15] proposed a twinlayer system to cultivate Chlorella vulgaris and Scenedesmus rubescens for the efficient removal of nitrates, phosphates and ammonium from municipal wastewater. Mulbry et al [16] set up a pilot-scale algal turf scrubber raceway to remove COD and BOD by using filamentous green algae grown in outdoor raceways at different loading rates of raw and anaerobically digested dairy manure effluent.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many technologies are currently in place to remove excess P from wastewaters, among them biological methods using phototrophic periphyton is a subject of great concern (Boelee et al, 2011;Guzzon et al, 2008;Roeselers et al, 2008;Shi et al, 2007;Sukačová et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…17 For instance, utilization of immobilized Chlorella vulgaris and Scenedesmus rubescens on a membrane system to remove nitrate from municipal wastewater was found to be efficient. 18 In addition, Wang et al 19 showed that employing immobilized Scenedesmus in calcium alginate as algal sheets is efficient in removal of ammonia nitrogen and orthophosphate from municipal wastewater. There have been few studies on the use of immobilized algae to remove color from dye solutions.…”
Section: ■ Introductionmentioning
confidence: 99%